1980
DOI: 10.1093/schbul/6.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Social Psychiatry in the United Kingdom: The Approach to Schizophrenia

Abstract: British contributions to theoretical and applied social psychiatry have been determined in large part by a traditional empiricism and by developments in social welfare legislation over the past 70 years. The establishment of a national health service covering the whole population and the attempt to provide comprehensive social services have created special opportunities for epidemiological research and for practical community psychiatry. These developments have by no means been uniform throughout the country, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Although it appears plausible to explain negative symptoms by frontal lobe dysfunction, it is unlikely that simple, localized frontal pathology can account for the presence of the admixture of symptoms usually found in schizophrenia (Wing etal., 1974;Wing, 1980). Moreover, the presence of neurologic soft signs and neuropsychological deficits, such as proprioceptive, gait, coordination, vestibular, eye tracking, and attentional (CPT) disturbances, suggest possible brain stem and cerebellar dysfunction (Holzman & Levy, 1977;King, 1974;Mirsky, 1969;Ornitz, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears plausible to explain negative symptoms by frontal lobe dysfunction, it is unlikely that simple, localized frontal pathology can account for the presence of the admixture of symptoms usually found in schizophrenia (Wing etal., 1974;Wing, 1980). Moreover, the presence of neurologic soft signs and neuropsychological deficits, such as proprioceptive, gait, coordination, vestibular, eye tracking, and attentional (CPT) disturbances, suggest possible brain stem and cerebellar dysfunction (Holzman & Levy, 1977;King, 1974;Mirsky, 1969;Ornitz, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall value of chi-square for the entire table is not statistically significant, the recovery rate alone shows a 10:1 advantage for the 'devotedly cared for' (x 2 for the row = 4-3, P < 005). Some of the 'devotedly cared for' may have received too much care which, according to Wing (1980), would militate against improvement. Leff(1978) has shown that patients exposed to a hostile critical environment relapse more frequently than those who returned to more favourable home situations.…”
Section: Social Factorsmentioning
confidence: 99%
“…The awareness that custodial institutions per se could play a detrimental role with respect to the quality of care delivered to mental patients is part of the knowledge that for many years (Zubin et al 1983) and in most countries has led to reforms aimed at assuring a flexible interaction between ambulatory and in-hospital settings (Redlich & Kellert, 1978;Wing, 1980). In Italy the 1978 Mental Treatment Act has completely rearranged the public care sector.…”
Section: Introductionmentioning
confidence: 99%